A companion to medical anthropology - Singer, Merrill; Erickson, Pamela I. (Pamela Irene), 1951- (Chichester, West Sussex ; Wiley-Blackwell, 2011)
'In a global environment of enormous health challenges, medical anthropologists offer important understandings of health systems and healing practices around the world. These leading international scholars assess our persisting problems of malnutrition, chronic and infectious diseases, and the influence of escalating levels of inequality, poverty, war, and genocide. A Companion to Medical Anthropology examines the key issues and controversies in medical anthropology today. Singer and Erickson present a thorough assessment of a specific area of medical anthropology, including expert overviews of major topics such as environmental health, global health, biotechnology, syndemics, nutrition, substance abuse, infectious disease, and sexuality and reproductive health. The authors also provide a guide to future trends and the emerging issues that will shape the future of medical anthropology and global health for years to come'--
Includes bibliographical references and index.
Keywords: Medical anthropology; SOCIAL SCIENCE / Anthropology / Cultural